Parasitaemia and fever in uncomplicated Plasmodium vivax malaria: A systematic review and individual patient data meta-analysis. - Emily S Groves; Julie A Simpson; Peta Edler; André Daher; Ayodhia P Pasaribu; Dhelio B Pereira; Kavitha Saravu; Lorenz von Seidlein; Megha Rajasekhar; Ric N Price; Robert J Commons; WorldWide Antimalarial Resistance Network (WWARN) P. vivax Fever Study Group (PLoS Neglected Tropical Diseases)
Background Parasite density thresholds used for diagnosing symptomatic malaria are defined by the relationship between parasitaemia and fever. This relationship can inform the design and development of novel diagnostic tests but appropriate parasitaemia thresholds for Plasmodium vivax malaria remain poorly defined. Methodology/principal findings We undertook an individual patient data meta-analysis of P. vivax clinical trials mapped to the WorldWide Antimalarial Resistance Network (WWARN) repository and used parasitaemia centiles of febrile patients at enrolment to derive proportions of patients who would have been diagnosed at different parasite densities. Febrile and afebrile patients with recurrent infections were selected to estimate pyrogenic densities using receiver operating characteristic curve analysis. In total 13,263 patients from 50 studies were included in the analysis. In 27 studies (8,378 febrile patients) in which a parasitaemia threshold was not applied as an inclusion criterion, the median parasitaemia at enrolment was 3,280/µL (interquartile range, 968 - 8,320); 90% of patients had a parasitaemia above 278/µL (10th centile), and 95% above 120/µL (5th centile). The 10th centile was higher in children <5 years old (368/µL) compared to adults ≥15 years (240/µL). In high relapse periodicity regions (Southeast Asia and Oceania) febrile patients presented with lower parasitaemias (10th centile 185/µL vs. 504/µL) and a wider range of parasitaemias compared to those from low relapse periodicity regions (interquartile range 760/µL - 8,774/µL vs. 1,204/µL - 8,000/µL). In total 2,270 patients from 41 studies had at least one episode of recurrent P. vivax parasitaemia, of whom 43% (849/1,983) were febrile at their first recurrence. The P. vivax pyrogenic density at first recurrence was 1,063/µL, defining fever with 74% sensitivity and 65% specificity. The pyrogenic density was lower in young children compared to adults ≥15 years (935/µL vs. 1,179/µL). Conclusions/significance The derived parasitaemia centiles will inform the use of current and the design of novel point-of-care tests to diagnose patients with symptomatic vivax malaria. Variation by age and location should be considered when selecting diagnostic thresholds and interpreting results. Trial registration This trial was registered with PROSPERO: CRD42021254905. The date of the first registration was 17th May 2021.